Tinjauan Yuridis Terhadap Kasus Wanprestasi dalam Perjanjian Kredit di Koperasi Tani Timiangan Raya, Desa Lubuk Napal, Kecamatan Rambah Samo, Kabupaten Rokan Hulu - Fernando, Akel (EL-EMIR Institute, 2025)
This study aims to analyze the legal aspects of a default case in the implementation of a credit agreement between members and the Timiangan Raya Farmers' Cooperative in Lubuk Napal Village, Rambah Samo District, Rokan Hulu Regency. Default is a violation of agreed-upon obligations, particularly in the case of a debtor's delay or inability to fulfill loan installment payments. This study uses an empirical legal method with a qualitative approach, based on primary data from interviews and cooperative documentation, as well as secondary data from laws and regulations and legal literature. The results indicate that the default in the cooperative occurred due to weak debtor feasibility analysis, internal oversight, and members' legal awareness. The cooperative's efforts to resolve the issue include a family approach, credit restructuring, and even termination of membership, but these efforts have not fully complied with dispute resolution mechanisms under contract law. This study recommends increasing the capacity of cooperative management and providing legal counseling to members to ensure that credit agreements are implemented fairly and effectively in accordance with the principles of contractual justice.